Investigation on converting 1-butene and ethylene into propene via metathesis reaction over W-based catalysts. Issue 15 (22nd February 2018) - Zuo, Guangzheng; Xu, Yuebing; Zheng, Jiao; Jiang, Feng; Liu, Xiaohao
Abstract : The molecular level mechanism for conversion of 1-butene and ethylene into desired propene over W/SBA-15 catalysts has been elucidated. Abstract : Supported W catalysts were extensively investigated for the conversion of 1-butene and ethylene into propene by metathesis reaction. The performance of catalysts was compared by using unsupported WO3, pure SBA-15, supported W/SBA-15 with different W loadings, varied calcination temperatures, and by changing the pretreatment gas atmosphere. The above catalytic results could be employed to deduce the reaction mechanism combined with characterization techniques such as BET, XRD, UV-vis DRS, Raman, pyridine-IR, XPS, and H2 -TPR. In this study, over the investigated W/SBA-15 catalysts, the results showed that the silanol group (Si–OH) in SBA-15 could act as a weak Brønsted acid site for 1-butene isomerization. However, the metathesis reaction was catalyzed by W-carbene species. The initially formed W-carbenes (WCH–CH3 ) as active sites were derived from the partially reduced isolated tetrahedral WO x species which contained WO or W–OH bonds in W 5+ species as corresponding Lewis or Brønsted acid sites. Furthermore, the W/SBA-15 being pretreated by H2 O led to a complete loss of the metathesis activity. This was mainly due to the sintering of isolated WO x species to form an inactive crystalline WO3 phase as demonstrated by XRD patterns. On the other hand, the reduction of WO x species remarkably suppressed by H2 O pretreatment was also responsible for the metathesis deactivation. This study provides molecular level mechanisms for the several steps involved in the propene production, including 1-butene isomerization, W-carbene formation, and metathesis reaction.